Disability-related bullying and its discursive formations and enactments in the social ecology of schooling. Issue 4 (4th July 2021) - Liasidou, Anastasia; Ioannidou, Elissavet
ABSTRACT: The study uses teachers' interview narratives to explore the relationship between childhood disability and bullying. Drawing insights from literature on childhood, critical disability studies and stigma-based perspectives on bullying, the latter is reconceptualised as being a socially mediated phenomenon, which is not only experienced by children – as either victims or perpetrators – but also as being constituted by them and their lived experiences of disability as 'difference'. The latter are usually shaped by negative depictions of disability in the social ecology of schooling that is responsible for giving rise to and exacerbating conditions within which bullying manifests Even though teachers are critical of the ways in which students with disabilities are victimised and acknowledge the role of schooling in creating the conditions within which bullying can occur, they nevertheless, inadvertently contribute towards the construction and perpetuation of 'disability as difference' discourse.